Analisis Pelaksanaan Assessment dalam Kurikulum Merdeka pada Pembelajaran IPS Kelas VII di SMP Negeri 2 Kota Solok - Noviana, Harisma Yoki; Eka Putri, Desi Armi (Jurusan PIPS FKIP UMMY Solok, 2023)
This research is motivated by the teacher's readiness to carry out assessments of students in the independent learning curriculum which has just been implemented at SMP Negeri 2 Solok City. The aim of this research is to determine the implementation of assessments on class VII social studies subjects at SMP Negeri 2 Solok City in facing the independent curriculum, the obstacles faced by class VII social studies teachers in implementing independent curriculum assessments, solutions to overcome the obstacles faced by class VII social studies teachers in implementing the independent curriculum assessment. The key informant for this research is the class VII social studies teacher and additional informants for this research are the school principal, curriculum representative and supervisor. Data collection was carried out through observation, interviews and documentation. Based on the research results, it can be concluded that SMP Negeri 2 Solok City has implemented assessment in accordance with the independent curriculum.